A High-Reliability RF MEMS Metal-Contact Switch Based on Al-Sc Alloy - Zhongxuan Hou; Yongkang Zhang; Chaowei Si; Guowei Han; Yongmei Zhao; Xiaorui Lu; Jiahui Liu; Jin Ning; Tongbo Wei (Micromachines, 2023)
This paper presents a new metal-contact RF MEMS switch based on an Al-Sc alloy. The use of an Al-Sc alloy is intended to replace the traditional Au-Au contact, which can greatly improve the hardness of the contact, and thus improve the reliability of the switch. The multi-layer stack structure is adopted to achieve the low switch line resistance and hard contact surface. The polyimide sacrificial layer process is developed and optimized, and the RF switches are fabricated and tested for pull-in voltage, S-parameters, and switching time. The switch shows high isolation of more than 24 dB and a low insertion loss of less than 0.9 dB in the frequency range of 0.1–6 GHz.